2014
DOI: 10.1126/scitranslmed.3007733
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Normalization of Neurological Disease after Intracranial Gene Therapy in a Feline Model

Abstract: Progressive debilitating neurological defects characterize feline GM1 gangliosidosis, a lysosomal storage disease caused by deficiency of lysosomal β-galactosidase. No effective therapy exists for affected children, who often die before age 5. In the current study, an adeno-associated viral vector carrying the therapeutic gene was injected bilaterally into two brain targets (thalamus and deep cerebellar nuclei) of a feline model of GM1 gangliosidosis. Gene therapy normalized β-galactosidase activity and storag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(94 citation statements)
references
References 49 publications
4
89
0
Order By: Relevance
“…Clinical rating scores and neurological assessment scores of large animal research models have been reported for gene therapy in feline models of the GM1 and GM2 gangliosidoses, 13,14 canine models of Duschenne muscular dystrophy, 15 and in rabbit and canine stroke models. [16][17][18] In the current project, we hypothesize that the neurological assessment score developed for the XLMTM dog model correlates with genotype and established measures of disease severity, such as hindlimb strength.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical rating scores and neurological assessment scores of large animal research models have been reported for gene therapy in feline models of the GM1 and GM2 gangliosidoses, 13,14 canine models of Duschenne muscular dystrophy, 15 and in rabbit and canine stroke models. [16][17][18] In the current project, we hypothesize that the neurological assessment score developed for the XLMTM dog model correlates with genotype and established measures of disease severity, such as hindlimb strength.…”
Section: Introductionmentioning
confidence: 99%
“…Efficacy of gene therapy in feline GM1 gangliosidosis using intracranial injection of b-galactosidase adeno-associated virus (AAV) vectors was quantified using MRI. McCurdy et al [2014] reported normalization of brain architecture and life span, and b-galactosidase activity in the brain and spinal cord of the AAV-treated cats.…”
mentioning
confidence: 95%
“…The comparison with AAV gene delivery to brain is difficult to establish as the resulting level of enzyme activity in different brain regions is measured in tissue blocks where the vast majority of cells are not transduced. Therefore the reported enzymatic activities of 10-to 100-fold above normal in different mouse [123,135] and cat [126,136] models of LSDs represent the activity of enzyme that is distributed throughout the brain from the target sites and now resides in non-transduced cells. Presently, there is no information on the degree of overexpression that takes place in AAV transduced cells in the target structures.…”
Section: Challengesmentioning
confidence: 99%
“…Two other clinical trials have tested AAV vectors carrying mammalian promoters such as the mouse phosphoglycerate kinase (PGK) promoter [120], or the rat neuron-specific enolase (NSE) promoter [121]. The choice of promoters is based on the availability of extensive data from pre-clinical studies in different animal models showing that AAV-mediated transgene expression under these promoters is stable and long lasting in the mammalian brain [122][123][124][125][126][127]. The stability of AAV gene expression in the human brain has been evaluated in clinical trials using an AAV2 vector encoding aromatic amino acid decarboxylase (AADC) injected into the putamen of Parkinson's disease patients [116], or children afflicted with AADC deficiency [115].…”
Section: Challengesmentioning
confidence: 99%
See 1 more Smart Citation